EVALUASI DAMPAK PROGRAM TAMAN BUDIDAYA TANAMAN OBAT KELUARGA (TOGA) PKK DI KELURAHAN CADIKA KABUPATEN BUNGO - Sari, Mela; Ramadinni, Fitria; Zahlimar, Zahlimar; Novriansyah, Yudhi (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2023)
The background of this research was the large number of TOGA PKK in Cadika subdistrict which were not still maintained, destroyed, and neglected. The realization of the TOGA PKK program was a form of concern for basic health assistance in the community by utilizing toga in the used of traditional medicines and the used of spices as ingredients for cooking ingredients which were still needed today. The aim of this research was to analyze the impact evaluation of the Toga PKK cultivation garden program in Cadika Village. The method used in this research was descriptive with a qualitative approach. The population in this study were Cadika Village officials, the Cadika Village PKK driving team, Dasawisma groups and the community. The total of analysis unit in this research were 15 people with the sampling technique was purposive sampling. The results of this research showed that the individual impact lead to positive things in facilitating the used of herbs and spices and even kitchen ingredients, gave a beautiful impression on the environment, Toga was used as opportunities for distributing herbal medicine but the cost and skills were limited. The organizational impact was that the TP PKK work program was hampered due to the non-achievement of the program's objectives whichwere part of the organization's work program. Meanwhile, the impact on the community, namely the community felt the impact of the PKK gown, made it easier for family members to obtain ingredients for the kitchen, basic assistance for minor illnesses suffered by family members and to beautify residents' yards with Toga plants. The impact of the social system tends to be in the interactions carried out by the community, the low motivation of the community in using the Toga was due to the lack of education about the use of the Toga cultivation garden which should be carried out by the TP PKK.